2019
DOI: 10.1177/1357633x18820374
|View full text |Cite
|
Sign up to set email alerts
|

National survey of telemedicine education and training in medical schools in France

Abstract: Introduction Telemedicine is a remote medical practice using information communication technology (ICT), and has been increasing in France since 2009. With all new forms of medical practice, education and training (ET) is required for quality and safety. To date, implementation of telemedicine ET has not been assessed in France. The objective of this study was to describe the implementation of telemedicine ET and evaluate the knowledge, attitudes and practices (KAP) of deans and associate deans from all medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 23 publications
(22 reference statements)
2
42
1
Order By: Relevance
“…Compared with countries such as Australia, which have relied heavily on telemedicine because of geographic limitations, the United States has much development to accomplish. However, compared with other countries such as France, the spread and reach of telemedicine training in undergraduate medical education is advance [26]. There therefore seems to be an important correlation between the state of telemedicine itself within a country, and the development of the educational system necessarily to effectively utilize telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with countries such as Australia, which have relied heavily on telemedicine because of geographic limitations, the United States has much development to accomplish. However, compared with other countries such as France, the spread and reach of telemedicine training in undergraduate medical education is advance [26]. There therefore seems to be an important correlation between the state of telemedicine itself within a country, and the development of the educational system necessarily to effectively utilize telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…VH became a necessity for the continuation of care. Lack of provider and staff education has been a key barrier to large-scale adoption of VH (4,9,11,15), and it needed to be addressed rapidly; therefore, our team developed and implemented a training program to support a new virtual model of care. Through its evaluation, opportunities were identified to optimize VH training moving forward.…”
Section: Discussionmentioning
confidence: 99%
“…The health system's inertia toward new models of care, lack of technology infrastructure, regulatory and legal issues, lack of financial incentives, and low tech-literacy have historically slowed implementation of VH (2). Furthermore, despite recommendations for VH training and core competencies (13,14), formal VH training programs are not widely established or studied (4,9,11,15). For patients, lack of access to technology and connectivity, privacy and security concerns, and low techliteracy hinder utilization of VH (11,12,16).…”
Section: Introductionmentioning
confidence: 99%
“…There is a range of studies on the incorporation of telemedicine into medical education which demonstrated positive and promising results, showing similar or better efficacy compared to traditional educational approach and high enthusiasm reported by the students [110]. The novel educational approach allows students to contact real patients and highly qualified specialists (lecturers) resulting in the improvement of clinical skills [111].…”
Section: Virtual Clinical Trialsmentioning
confidence: 99%